The relationship between landscape and meteorological parameters on COVID-19 risk in a small-complex region of Yogyakarta, Indonesia - Purwantara, Suhadi; Ashari, Arif; Putro, Sutanto Tri Juni (Bulletin of Geography. Physical Geography Series, 2021)
As of the beginning of September 2021, the COVID-19 outbreak has lasted for more than 1.5 years in Indonesia, especially on Java and Bali islands. Yogyakarta Special Region, Indonesia, is one of the areas that continued to impose restrictions on community activities at the highest level for that period. This is due to the high rate of COVID-19 spread in this region. In this paper, the influence of landscape and meteorological parameters on the spread of COVID-19 risk in Yogyakarta is investigated. This study utilises primary and secondary data obtained from observation, remotesensing-image interpretation, literature study and data documented by several agencies. The data were statistically analysed using simple linear regression and Geographic Information System (GIS) analysis utilizing the average nearest neighbour. The results show that the variation in landscape and meteorological parameters in the Yogyakarta area does not have a significant impact on the spread of COVID-19. Ease of accessibility in various areas of Yogyakarta is able to overcome landscape barriers. This affects the random distribution pattern of COVID-19, clustering in plain areas that facilitate population mobility rather than in mountainous, volcanic or karst areas. Also, meteorological conditions with small variations do not impact the spread of COVID-19. In summary, this study shows that ease of mobility in a medium-wide area can encourage the spread of COVID-19 in various regions even though there are variations in its terrain and climate.